Study of sensing technologies for machine tools. (August 2016) - Fujishima, Makoto; Ohno, Katsuhiko; Nishikawa, Shizuo; Nishimura, Kimiyuki; Sakamoto, Masataka; Kawai, Kengo
Abstract: Technologies for machine tools have been rapidly developed in recent years. Innovative technologies are expected to be developed in the electronics and information fields with the trend of industry 4.0 or IoT, which will significantly contribute to the development of control technologies for machine tools. This paper describes approaches to sensing technologies which can be practically used on machine tools. The sensing system used in this study was developed to obtain a huge volume of sensing data about cutting conditions. By this system, we are studying innovative technologies of machine tools to improve cutting efficiency and sensing technologies for coolant level using machine learning.